Pope Francis as a Global Actor Where Politics and Theology Meet (Palgrave Studies in Religion, Politics, and Policy, 2018)
Pope Francis confuses many observers because his papacy does not fit neatly into any pre-established classificatory schemes. To gain a deeper appreciation of Francis's complicated papacy, this volume proposes that an interdisciplinary approach, fusing concepts derived from moral theology and the social sciences, may properly situate Pope Francis as a global political entrepreneur. The chapters in this volume ask what difference it makes that he is the first pope from Latin America, how and why different countries in the world respond to him, how his understanding of scripture informs his ideas on economic, social, and environmental policy, and where politics meets theology under Francis. In the end, this volume seeks to provide a more robust understanding of the enigmatic papacy of Francis.